Psychological impact of COVID-19 on the Ecuadorian population: a comparative analysis 1 year after quarantine measures - Gallardo-Rumbea, Jorge Andrés; Farfán Bajaña, María José; Mautong, Hans; Moncayo-Rizzo, Jorge; Andrade, Derly; Cherrez-Ojeda, Ivan; Alvarado-Villa, Geovanny (Frontiers in Psychology, 2024)
Introduction Social isolation during and after the COVID-19 pandemic has sparked interest in its psychological and neurobiological consequences. The pandemic has been associated with an increase in anxiety, depression, and stress, according to some cross-sectional studies. This study aims to analyze changes in the levels of anxiety, depression and stress by comparing the confinement phase to the post-confinement period in the Ecuadorian population. Methods A longitudinal, comparative, prospective study was conducted using an online survey comprising two sections. The first section gathered demographic information, whereas the second section included the DASS-21 questionnaire. Ecuadorian participants who completed the survey during the initial data-collection period were included. Results In total, 162 participants were included in the final analysis. The average age of the participants was 29.6 ± 11.7 years, and the majority were women (63.3%). In 2020, the median depression, anxiety, and stress scores were 6 (IQR 2–12), 6 (IQR 2–10), and 10 (IQR 6–16) respectively. In 2021, the median depression score was 8 (IQR 4–14), the median anxiety score was 8 (IQR 4–14.5), and the median stress and its interquartile range were 10 (IQR 6–18). The levels of depression, anxiety, and stress were significantly inversely correlated with age, number of children, self-reported general health, and self-reported mental health in both 2020 and 2021. Conclusion Exercise, being a student, sex and having had COVID-19 examination may be predictors for the changes in the levels of psychological disorders. Implementing psychological strategies, such as cognitive behavioral therapy, and physiological interventions, like regular physical activity, early in the post-lockdown period could help mitigate the negative mental health impacts observed in the aftermath of the pandemic. These interventions can provide necessary support and coping mechanisms for those at higher risk, thereby improving overall mental health outcomes.